Performance Assessment of Crash Barriers used in Road Safety: A Case Study of Malekhu Kurintar Section of the Prithvi Highway - Bati, Saru; Shahi, Thusitha Chandani (Journal of Science and Engineering, 2020)
Hill roads in Nepal are comprised of critical geometry and limited roadway clearances. It causes high number of runoff roadway type of accidents with single vehicle. These accidents often carry huge number of fatalities and severe injuries. Installation of crash barriers is the most effective way of preventing such accidents along hill roads. However, the existing practice of construction of crash barriers does not show the satisfactory results. Therefore, this research aimed at the evaluation of typical crash barriers constructed along the valley side of highway. Analysis of the road accident of Malekhu-Kurintar section of Prithvi Highway record shows that this section has relatively higher accident rate and most of the accidents are runoff roadway type. Further, these accidents are mainly caused due to either the absence or the failure of the crash barriers along the valley side of the highway. On the basis of field records, kinetic energy absorbed by the crash barriers and their deflections was investigated by application of computer based analysis tool ABAQUS V6.10. It has given satisfactory results on the deflection of W-beam and plum concrete barriers due to the impact of vehicle moving in various range of speed.